Cerebral Palsy and Neonatal Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The type and severity of cerebral palsy (CP) and pattern of associated disability in children with or without preceding neonatal encephalopathy (NE) were compared in a population-based case-control study of patients followed for 6 years at the Children's Hospital, Westmead, Sydney, Australia.